Pengaruh Customer Experience, Kualitas Produk dan Inovasi Produk terhadap Repurchase Intention pada Wanita Pengguna Hijab Produk Rabbani - Hasanawi, Hasanawi; Fadilah, Kartika Nurul; Yuliawati, Yupi; Yawahar, Jon; Mulyadi, Maheran (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
The development of the fashion world makes women who wear hijabs can appear fashionable and trendy. It is not surprising that hijab entrepreneurs compete to make hijabs with product designs and product quality that are in accordance with fashion trends and competitive prices. Currently, there are many entrepreneurs who sell hijab products with various brands, one of which is Rabbani. Rabbani is one of the first instant headscarf companies in Indonesia to release flagship products in the form of instant headscarves and various other Muslim products. This study aims to determine the effect of customer experience, product quality, and product innovation on repurchase intention in women who use Rabbani hijab products. This study uses a quantitative method with a descriptive and verification approach. The primary data collection technique by distributing questionnaires developed based on research variable indicators to a sample of 385 respondents. Data were analyzed using descriptive and verification methods. The results of the study above indicate that respondents' assessments of customer experience, product quality, product innovation, and repurchase intention are in the high category, meaning that respondents agree with the positive statements on each indicator in each variable. The results of the verification analysis indicate that the variables of customer experience, product quality, and product innovation have a positive and significant effect on repurchase intention in women who use Rabbani hijab products, both partially and simultaneously. The magnitude of the influence of the variables of customer experience, product quality, and product innovation on repurchase intention is 61% and the remaining 39% is influenced by other variables not examined in this study.